A Decade of Quality Management System at the Maribor Public Library - Sirk, Irena; Popović, Sabina Fras (Qualitative and Quantitative Methods in Libraries; Vol 4 No 2 (2015): June 2015 Issue, 2017)
In 2005, the Maribor Public Library, the second largest public library in Slovenia, was the first Slovenian public library that introduced its library operations in accordance with the requirements of the international standard Quality Management System ISO 9001: 2000. The paper presents the findings of a ten-year research. Three evaluation methods of the quality management system according to ISO 9001:2000 and ISO 9001:2008 were applied in the library operations as recommended: internal audit, external audit and management review. The effects of adopted and fulfilled recommendations are presented. An overview of the results also highlights those recommendations that have not been included in the library operations and the reasons for such a decision. The data is presented qualitatively and quantitatively. On this basis, an analysis of the impact of library management is carried out in accordance with the requirements of the international standard Quality Management System ISO 9001:2008 and eight management principles that are the basis of that standard. In the last part of the article, the orientation of the Maribor Public Library by using the international standard Information and documentation -- Methods and procedures for assessing the impact of libraries SIST ISO 16439:2014(E) is suggested. The article also presents those recommendations of the evaluation method of quality management system in accordance with ISO 9001:2008 (internal audit, external audit and management review) which have guided the library in the past five years within the external assessment to demonstrate its impact on the environment.